ANALYSIS OF POINT CONTACTS USING THE COMBINED BOUSSINESQ-CERRUTI PROBLEM - Stefan GHIMISI (Fiabilitate şi Durabilitate)
For "non-conforming" contact where deformations are small enough compared to body dimensions, the theoretical elasticity will apply to the closed contact defined by the contact area.The tension can be calculated by considering each body as a solid semiinfinite, limited by a flat surface, that is to say a semisphere of elasticity. This idealization, where the bodies have the surface of the arbitrary profile and seen as a semifinished extension is almost universal for the elastic contacts.Tensions and displacements in the elastic semisphere can determine surface tractions being deduced for the first time by Boussinesq (1885) and Cerruti (1882) who have made the theory of potential, and this approach is presented by Love as well (1957)